Resilience of agro-industrial regions in the Volga Federal District to import supply restrictions - Elshin Leonid; Mingulov Almaz; Abdrakhmanova Dilyara (E3S Web of Conferences)
Resilience theory offers a critical framework for addressing risks posed by sanctions and external shocks. While extensively studied at the macroeconomic level, significant methodological gaps persist at the meso-economic level, particularly in agrarian-focused regions. This study develops strategic guidelines and management models to enhance the resilience of meso-level economic systems in the Volga Federal District, with a focus on agro-industrial entities. By systematizing and adapting existing approaches, the study introduces a novel methodology for assessing regional resilience to external shocks. This method evaluates two key dimensions: vulnerability and recovery efficiency. The findings provide actionable insights for improving regional shock resilience, contributing to sustainable development and food security amid evolving foreign economic relations.